PENGARUH LIKUIDITAS DAN PERPUTARAN MODAL KERJA TERHADAP NET PROFIT MARGIN PADA PERUSAHAAN ROKOK YANG LISTING DI BURSA EFEK INDONESIA - B11109090, Tri Utami (Jurnal Manajemen Update, 2014)
This research is performed to determine the development of the average Current Ratio, Quick Ratio, Working Capital Turnover, Return On Working Capital and Net Profit Margin for the period of 2007 - 2011 and also to determine the effect of the Current Ratio, Quick Ratio, Working Capital Turnover, and Return On Working Capital The Net Profit Margin. Object of the research is that cigarette companies listing on the Indonesia Stock Exchange (the period of 2007-2011). The method used is in the form of descriptive statistical describe and analyze existing data. The analytical method used is multiple linear analysis using SPSS version 16.0. The results of this research indicate that four variables simultaneously very significant effect on The Net Profit Margin. The results of this study indicate that four variables simultaneously very significant effect on The Net Profit Margin with a significant level of Î± = 0.05. In partial, Current Ratio, Return On Working Capital and Working Capital Turnover is a significant effect on The Net Profit Margin, while the quick ratio variables, no significant effect on The Net Profit Margin.Test results of determination (R2) shows the independent variable is able to explain the variability in The Net Profit Margin of 0.580, which means 58% of the independent variables, while the remaining 42% are all factors that are not included in this research model. Keywords: Current Ratio, Quick Ratio, Working Capital Turnover, Return On Working Capital and Net Profit Margin